Modeling and Optimization of Propane Selective Oxidation to Acrylic Acid Over Mo 1 V 0.3 Te 0.23 NB 0.12 O X Catalyst Using Artificial Neural Network and Box-Behnken Design - Mazloom, Golshan (Chemical Engineering Research Bulletin, 2020)
The prediction capability of response surface methodology (RSM) and artificial neural network (ANN) models for propane selective oxidation to acrylic acid (AA) over Mo1V0.3Te0.23Nb0.12Ox catalyst was investigated in this work. 15 experimental runs based on the Box-Behnken design (BBD) were employed to study the effects of temperature (380 to 500 °C), superficial velocity (33.3 to 66.7 mL (min gcat)-1), (O2)/(C3H8) ratio (1 to 3) and their interactions on propane conversion, AA selectivity and COx selectivity. The quadratic polynomial BBD equations and the feed-forward back propagation ANN models were developed based on the designed experimental data. Statistical analysis; coefficient of determination (R2), mean absolute error (MAE) and analysis of variance (ANOVA) illustrated that there was acceptable adjustment between BBD and ANN predicted responses as compared to experimental data. While, the ANN model showed a clear preference and generalization capability over BBD model in the case of experimental data set which were not used to training the models. In addition the optimum conditions were found to be temperature (461.7 °C), GHSV (51.9 mL (min gcat)-1) and (O2)/(C3H8) ratio (2.1) which were determined by desirability function approach. In these conditions, propane conversion of 15.2%, AA selectivity of 32% and COx selectivity of 44% which obtained experimentally were in reasonable agreement with predicted responses. Chemical Engineering Research Bulletin 21(2019) 1-19